Rediscovering a ’lost’ village of al-ʿAyn: archaeology and communal memory in the oasis (poster) - Sheehan, Peter; Power, Timothy; Al Kaabi, Omar; Khalifa, Mohamed; al-Dhaheri, Mohamed; al-Mansoori, Bakheeta; al-Zaabi, Leqa; al-Dhaheri, Myriam; al-Mansoori, Rifaa (Proceedings of the Seminar for Arabian Studies, 2015)
The Historic Environment Department of TCA Abu Dhabi has recently completed the first stage of a project aimed at investigating and presenting to the public the historic village of al-Khrays, at the southern edge of al-Jīmī Oasis in the city of al-ʿAyn. From the late 1960s onwards, the city of al-ʿAyn witnessed the gradual abandonment of the villages located around the oases and the shift of their communities to newly built housing quarters, often in close proximity to the earlier settlements. These old settlements gradually fell into disuse and disrepair and were eventually demolished and largely forgotten. Through a combination of ethnographic interviews and archaeological excavation, Abu Dhabi TCA is now recording, investigating, and protecting the remains of these settlements, many of which lie within the area of the newly inscribed UNESCO World Heritage Site of Al Ain (al-ʿAyn). The poster will present the results of the excavations and finds, including a typological quantification of a late Islamic ceramic assemblage dating from the late nineteenth to the mid-twentieth century, undertaken with the involvement of Zayed University students.